Papacy and church : the assertion and reception of Papal authority and justice in the Papal letters, 1143-53 - Carlson, Frank (Trinity College (Dublin, Ireland). Department of History, 2007)
The subject of this thesis is papal authority and administrative practice in the period 1143-53, and how they are reflected through the letters of the papacy. Accordingly, the focus here is on the everyday business of the papacy and how its authority was expressed and at the same time received and utilised by the Church. As a result, the broader question of the curia's own territorial-political 'policy' is here largely left aside. With that said, the curia enjoyed a decade of relative peace, both in respect to an absence of schism, or contending popes, and with regard to most of the great secular princes. And accordingly the papacy's own self-expression of authority tended to be benign: the curia tended to treat its own authority and primacy as something so firmly established that it seldom required fervent or peremptory articulation.
Keywords: Medieval History, Ph.D.; Ph.D. Trinity College Dublin